Self-navigated multishot echo-planar pulse sequence for high-resolution diffusion-weighted imaging. - Nunes, R; Jezzard, P; Behrens, T; Clare, S (2005)
Single-shot techniques have preferentially been adopted for diffusion-weighted imaging due to their reduced sensitivity to bulk motion. However, the limited spatial resolution achievable results in orientational signal averaging within voxels containing a distribution of fibers. This leads to impaired performance of tracking algorithms. To combat partial volume effects, high-resolution multishot techniques can be used but, being more sensitive to motion, require phase correction to obtain artifact-free images. While separately acquiring 2D navigator echoes is an effective approach, it is not very efficient as the navigators do not contribute signal to the final image. Here a self-navigated interleaved echo planar imaging (EPI) sequence based on EPI with keyhole (EPIK) is proposed. The refocusing reconstruction method is successfully adapted to EPIK and compared to the standard linear approach. The resultant improvement in resolution is shown to lead to a significant increase in anisotropy in fiber-branching areas and can potentially offer a superior ability to detect fine tract splits.